Distress in institutionalized profoundly handicapped children a study of manifestations and causes of distress and nursing interventions to relieve them. - Santos, Gay Oyco
This is an exploratory study done on 26 profoundly handicapped children who were confined in a long-term care institution in New York City. It sought to answer the following questions: (1) Do all profoundly handicapped children manifest distress; (2) What are the manifestations of distress in profoundly handicapped children; (3) What are the causes of distress in profoundly handicapped children; and (4) What are the nursing interventions commonly utilized by members of the nursing staff to alleviate distress in profoundly handicapped children? The children in this study was observed by modified sampling by the researcher and a trained observer, each child being observed for a total of 60 minutes. Observations were recorded narratively on a process recording tool. Observations which contained distressful situations were taken as sample for the study. Interview of each of the 23 members of the nursing staff was done after observation. A semi-structured interview schedule was constructed to find out how frequent each child manifested distress, the manifestations, usual causes and nursing interventions they did to relieve distress. Nurses' notes written over the past 3-month period were also reviewed and analyzed for documentation of distressful situations. All data were subjected to content analysis and were further analyzed by frequency and percentage distributions. Initial attempts were made to establish statistically significant relationships between selected variables and distress reports and manifestations. Findings are: 1. All profoundly handicapped children manifested distress 1 way or the other, only others manifested distress more frequently than the rest. 2. Distress was manifested a. in vocalization, mainly by crying; b. in body movement, mainly by restlessness or general hyperactivity; c. in facial appearance, mainly in the form of tears; and d. in physiologic responses, mainly by lack of appetite. 3. Among the 22 identified causes of distress, 14 (64 ) were physical in nature. 4. There were 26 nursing interventions reported regardless of cause and for every cause identified there was as many as 13 interventions reported. A Distress Assessment Checklist for profoundly handicapped children was developed from this study. This checklist needs to be tested in the future for reliability and validity.